From Theory to Practice: Exploring the Synergy between Chemo-Entrepreneurial-Motivated-Approach and Students’ Achievement in Senior Secondary Chemistry Practical - Saibu, Sakibu O.; Oludipe, Olajumoke S.; Owolabi, Tunde; Adam, Umar; Oladejo, Adekunle I.; Olude, Adebisi S.; Ogundowole, Ayodeji (Journal of Educational Sciences, 2025)
This study addresses the persistent challenge that impedes meaningful learning and acquisition of practical skills in chemistry due to the limitations of traditional teaching methods. It explored the potency of the Chemo-Entrepreneurial-Motivated-Approach (CEMA) in enhancing senior secondary students’ achievement in chemistry practical. A non-randomized pre-test, post-test quasi-experimental design with a 2x2 factorial matrix was used, involving 118 senior secondary II students from two purposively selected secondary schools using two intact classes in Education District V, Lagos State, Nigeria. The experimental group (58 students) received CEMA-based instruction, while the control group (60 students) was taught using the lecture method over seven weeks. Data collected through the Chemistry Practical Achievement Test (reliability index = 0.76) were analyzed using mean, standard deviation and analysis of covariance. Results revealed that students taught with CEMA significantly outperformed those in the lecture method group, indicating that CEMA effectively improved practical skills and achievement (F(1,113)=24.55; p<0.05). However, no statistically significant gender differences [F(1,56)=.08; p>0.05] and interaction effects between the treatment and gender were observed [F(1,113)=.25; p>0.05]. The study concluded that CEMA enhanced students’ achievement and skills in chemistry practical, and recommended its adoption in senior secondary school chemistry instruction to improve students’ achievement and entrepreneurial competence.